Pengenalan Lambang Palang Merah dan Bulan Sabit Merah Pada Hut Pmi Ke 77 di Kota Medan - Aldiansyah Siregar; Febri Elsa Manora; Kiki Khairuni; Nurkhadijah Hasibuan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Indonesian Red Cross (PMI) is a national association organization in Indonesia which is engaged in social humanity. The Indonesian Red Cross in Medan City has been established since the 1950s, since then PMI Medan City has spread kindness to the people of North Sumatra, especially Medan City through disaster management, blood donations, social assistance and coaching the younger generation and so on. The purpose of this research is to find out about the views and knowledge or perspectives of the Medan city community about PMI. This research is a type of qualitative research that uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The results of the study show that the breadth of understanding of the Medan city community about PMI and the various views or perspectives of the community towards the Medan city PMI. Indonesia has had a national association of the Red Cross movement since 1950 through Presidential Decree No. 25 of 1950. The use of the Red Cross symbol can also lead to perceptions in some circles of society such as that the symbol is connoted as a religious organization which means it was founded on the basis of a religion. In this case the researcher used a qualitative method in the form of interviews to find out the use of the red cross, red crescent emblem. From the results of research on the use of the red cross symbol in the community, especially Deli Serdang, they have not been able to recognize it properly. Only a few know the PMI symbol, this is because the community does not yet know the PMI symbol. So the introduction of the PMI symbol in the Deli Serdang Community must be increased again so that the use of the Red Cross or Red Crescent Emblem itself in Indonesia can be regulated clearly based on the Red Cross Affairs Law.